Comfort evaluation of ZnO coated fabrics by artificial neural network assisted with golden eagle optimizer model - Amor, Nesrine; Noman, Muhammad Tayyab; Petru, Michal; Sebastian, Neethu (Scientific reports, 2022)
This paper introduces a novel technique to evaluate comfort properties of zinc oxide nanoparticles (ZnO NPs) coated woven fabrics. The proposed technique combines artificial neural network (ANN) and golden eagle optimizer (GEO) to ameliorate the training process of ANN. Neural networks are state-of-the-art machine learning models used for optimal state prediction of complex problems. Recent studies showed that the use of metaheuristic algorithms improve the prediction accuracy of ANN. GEO is the most advanced methaheurstic algorithm inspired by golden eagles and their intelligence for hunting by tuning their speed according to spiral trajectory. From application point of view, this study is a very first attempt where GEO is applied along with ANN to improve the training process of ANN for any textiles and composites application. Furthermore, the proposed algorithm ANN with GEO (ANN-GEO) was applied to map out the complex input-output conditions for optimal results. Coated amount of ZnO NPs, fabric mass and fabric thickness were selected as input variables and comfort properties were evaluated as output results. The obtained results reveal that ANN-GEO model provides high performance accuracy than standard ANN model, ANN models trained with latest metaheuristic algorithms including particle swarm optimizer and crow search optimizer, and conventional multiple linear regression.
Keywords: Algorithms; oxid zinečnatý; textilie; propylaminy; Eagles; Propylamines; Sulfides; Zinc Oxide; Animals; Textiles; Accipitridae; sulfidy; Neural Networks, Computer; algoritmy; zvířata; neuronové sítě